Locating Boko Haram in the Global War on Terror - Oyateru Babatunde (Covenant University Journal of Politics and International Affairs, 2023)
The September 11th attacks on the World Trade Centre and Pentagon in the United States in 2001 ushered the world into an era marked by increasing focus on terrorism and counterterrorism and introduced the world to the Global War on Terror (GWOT). The GWOT has significantly militarized the foreign policy of the United States and many other nations. In the decades that have followed the September 11 attacks, the GWOT has lost its discursive currency. However, its legacy is still very apparent, especially in Sub-Saharan Africa, which had not previously experienced terrorism. Most notably, Boko Haram in Nigeria has risen to become one of the deadliest terrorist groups in the world. Guided by three questions, the article establishes the linkages between Boko Haram and the GWOT, explores Mary Kaldor’s New War thesis in relation to this relationship and explores the conditions that have sustained the legacy of the GWOT. Theoretical arguments on securitization theory, greed and grievance theory shape the discussion.